(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To investigate the spectrum and drug sensitivity of pathogenic bacteria in children presenting with septicemia. Methods: A retrospective analysis was performed on the spectrum and drug sensitivity of pathogenic bacteria in 450 children (age0— 5 years) with septicemia, who were admitted from January to December, 2014. Results: A total of 450 blood culture samples were collected. Out of these 30% were cultures positive. Gram negative bacteria were 63%of total isolates and gram positive were 37%.The commonest gram negative bacterial isolates were E Coli(22%) followed by Klebsiella (11%) , acintobacter (9%) , pseudomonas (8%) ,salmonella typhi (6%) ,salmonella paratyphi (4%) and hemophillus influenza type B(3%).Among the gram positive organisms commonest organisms were staphylococcus aureus (15%), staphylococcus epidermidis(10%) , methicillin resistant staphylococcus (MRSA) (7%) and pneummococcus (5%) . Conclusion: E Coli was the most commonly isolated pathogen in pediatric age group less than 5 years sensitive to third generation cephalosporins and aminoglycosides(1).Commonest gram positive isolate was staphylococcus aureus which was sensitive to amoxicillin + clavulanic acid, aminoglycosides and vancomycin .